2021
DOI: 10.3389/fcvm.2021.609300
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of miR-205/P4HA3 Following Angiotensin II-Induced Atrial Fibrosis: Implications for Atrial Fibrillation

Abstract: Objective: Atrial fibroblasts are the main component of atrial fibrosis. Data in previous studies proved the implication of miRNAs in AF progression and the association of miR-205 with cancer associated-fibroblasts, while no evidence supported the implication of miR-205 in atrial fibrosis. Therefore, this study aims to explore the effect and mechanism of miR-205/P4HA3 axis on atrial fibrosis.Methods: Angiotensin II (Ang II) was used to induce atrial fibrosis model in rats, which was verified by H&E sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Evidence has shown that miR-205 is poorly expressed in angiotensin II-induced rat atrial fibrosis models [ 18 ]. Meanwhile, there were significant increases in EHMT2 expression and H3K9 methylation levels in TGF-β1-induced renal fibrosis mice and bleomycin-induced pulmonary fibrosis mice [ 20 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that miR-205 is poorly expressed in angiotensin II-induced rat atrial fibrosis models [ 18 ]. Meanwhile, there were significant increases in EHMT2 expression and H3K9 methylation levels in TGF-β1-induced renal fibrosis mice and bleomycin-induced pulmonary fibrosis mice [ 20 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Investigations on these miRNAs shed light on the molecular mechanisms in the etiopathogenesis of AF and suggest miRNA targeting to be an appealing strategy for the treatment and management of this disorder [ 17 ]. Among these miRNAs, miR-205 has been recently illustrated to affect the progression of AF by regulating the functions of rat fibroblasts [ 18 ]. Meanwhile, miR-205-5p can act as an inhibitor of oxidative stress and inflammation in hypoxia/reoxygenation-injured rat hippocampal neurons [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, microRNA-181a has been demonstrated as an anti-fibrotic factor in fBMFs [ 54 ], and participated in TGF-β-induced EMT in hepatocytes [ 55 ]. As for miR-205, it was found to attenuate the angiotensin II-induced fibrosis in vivo and myofibroblast activation in atrial fibroblasts [ 56 ]. Given that we observed the decreased myofibroblast activities and TGF-β/Smad2 signaling in fBMFs with sh-lincROR, whether lincROR contributes to the development of OSF via functioning as a competing endogenous RNA of microRNA-145, microRNA-181, or miR-205 requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…egy to prevent or treat atrial fibrosis or AF in DCM. Reducing miR-205 expression in AF rats attenuated atrial fibrosis by targeting prolyl-hydroxylase α polypeptide III (P4Hα3) to inhibit CF proliferation and migration and inactivating the JNK pathway [29]. Other miRNAs are also involved in atrial remodeling, including miR-133, miR-590 and miR-146b-5p, and all were downregulated in a canine model of AF [30,44].…”
Section: Atrial Fibrosismentioning
confidence: 99%